"We don't have time for that carry-on anymore" – Protest and the construction of space at Waitangi in the 1980s - Schmidt, Tyson (Architectural History Aotearoa, 2009)
The 6th of February is New Zealand's annual day of cultural performance par excellence. It is not a rememberance and reflection of what is undoubtedly this country's most important historical moment, but instead an enactment of contemporary understandings of the Treaty of Waitangi by both Māori and the Crown. Architecturally this performance is played out at, and between, Te Tii marae and the Treaty grounds at Waitangi. The partnership between Māori and the Crown is spatially expressed each year by symbolically important rituals being conducted and protocols observed at each specific site. People gather, welcomes occur, addresses are given, entertainment provided, bridges crossed, debates take place, demands are made, and protests held. The actions of the various parties are frequently beamed into households by the television networks and reported in the national newspapers, leading to a national construction of space that represents current perceptions of cultural and race relations. The 1980s saw a significant shift in the construction of Waitangi as space. Following the rise of the land rights movement in the 1960s and 1970s, Māori activists focussed their efforts on Waitangi and Waitangi Day more than ever before. The government responded by denying access to the Treaty grounds, then retreating from Waitangi celebrations, and then eventually returning by the end of the decade. Waitangi as space became a pawn in a political contest, and its place in the national psyche moved with each action and counter-action.